Alteration in the Lipid Profile and the Desaturases Activity in Patients With Severe Pneumonia by SARS-CoV-2 - Pérez-Torres, Israel; Guarner-Lans, Verónica; Soria-Castro, Elizabeth; Manzano-Pech, Linaloe; Palacios-Chavarría, Adrián; Valdez-Vázquez, Rafael Ricardo; Domínguez-Cherit, Jose Guillermo; Herrera-Bello, Hector; Castillejos-Suastegui, Humberto; Moreno-Castañeda, Lidia; Alanís-Estrada, Gabriela; Hernández, Fabián; et al. (Frontiers in Physiology, 2021)
The kidnapping of the lipid metabolism of the host’s cells by severe acute respiratory syndrome (SARS-CoV-2) allows the virus to transform the cells into optimal machines for its assembly and replication. Here we evaluated changes in the fatty acid (FA) profile and the participation of the activity of the desaturases, in plasma of patients with severe pneumonia by SARS-CoV-2. We found that SARS-CoV-2 alters the FA metabolism in the cells of the host. Changes are characterized by variations in the desaturases that lead to a decrease in total fatty acid (TFA), phospholipids (PL) and non-esterified fatty acids (NEFAs). These alterations include a decrease in palmitic and stearic acids (p ≤ 0.009) which could be used for the formation of the viral membranes and for the reparation of the host’s own membrane. There is also an increase in oleic acid (OA; p = 0.001) which could modulate the inflammatory process, the cytokine release, apoptosis, necrosis, oxidative stress (OS). An increase in linoleic acid (LA) in TFA (p = 0.03) and a decreased in PL (p = 0.001) was also present. They result from damage of the internal mitochondrial membrane. The arachidonic acid (AA) percentage was elevated (p = 0.02) in the TFA and this can be participated in the inflammatory process. EPA was decreased (p = 0.001) and this may decrease of pro-resolving mediators with increase in the inflammatory process. The total of NEFAs (p = 0.03), PL (p = 0.001), cholesterol, HDL and LDL were decreased, and triglycerides were increased in plasma of the COVID-19 patients. Therefore, SARS-CoV-2 alters the FA metabolism, the changes are characterized by alterations in the desaturases that lead to variations in the TFA, PL, and NEFAs profiles. These changes may favor the replication of the virus but, at the same time, they are part of the defense system provided by the host cell metabolism in its eagerness to repair damage caused by the virus to cell membranes.